Understanding the Effects of High Pressure on Bacterial Spores Using Synchrotron Infrared Spectroscopy - Modugno, Chloé; Peltier, Caroline; Simonin, Hélène; Dujourdy, Laurence; Capitani, Francesco; Sandt, Christophe; Perrier-Cornet, Jean-Marie (Frontiers in Microbiology, 2020)
Bacterial spores are extremely resistant life forms that play an important role in food spoilage and food-borne disease. The return of spores to a vegetative cell state is a three-step process, these being activation, germination and emergence. High Pressure (HP) processing is known to induce germination in part of the spore population and even to inactivate a high number of Bacillus spores when combined with other mild treatments such as the addition of nisin. The aim of the present work was to investigate the mechanisms involved in the sensitization of spores to nisin following HP treatment at ambient temperature or with moderate heating leading to a heterogeneous spore response. Bacillus subtilis spores were subjected to HP treatment at 500 MPa at 20 °C and 50 °C. The physiological state of different subpopulations was characterized. Then Fourier transform infrared (FTIR) microspectroscopy coupled to a synchrotron infrared source was used to explore the heterogeneity of the biochemical signatures of the spores after the same HP treatments. Our results confirm that HP at 50 °C induces the germination of a large proportion of the spore population. HP treatment at 20 °C generated a subpopulation of ungerminated spores reversibly sensitized to the presence of nisin in their growth medium. Regarding infra-red spectra of individual spores, spores treated by HP at 50 °C and germinated spores had similar spectral signatures involving the same structural properties. However, after HP performed at 20 °C, two groups of spores were distinguished; one of these groups was clearly identified as germinated spores. The second group displayed a unique spectral signature, with shifts in the spectral bands corresponding to changes in membrane fluidity. Besides, spores spectra in the amid region could be divided in several groups close to spectra properties of dormant, germinated or inactivated spores. The major contributions to the spectral variation between spores treated by HP at 20°C spores and other populations are localized at wavenumber corresponding to 𝝰-helix and 𝝱-structures. These changes in the lipid and in the amid regions could be the signature of reversible changes linked to spore activation.